2016
DOI: 10.3892/ijo.2016.3785
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PD-L1 expression in a high-grade invasive human oral squamous cell carcinoma microenvironment

Abstract: Blockade of the programmed-death 1 receptor (PD-1)/programmed-death ligand (PD-L1) pathway efficiently reduces tumour growth and improves survival. Durable tumour regression with blockade of the PD-1/PD-L1 checkpoint has been demonstrated in recent clinical studies. Oral squamous cell carcinoma (OSCC) is highly immunosuppressive, and PD-L1 expression has been proposed as a potential mechanism responsible for this phenotype. Despite the fact that anti-PD-1 treatment can produce durable responses, such therapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 50 publications
6
70
0
Order By: Relevance
“…Many recent studies have highlighted the critical role of PD-L1 in regulating the biological functions of cancer cells themselves, including cell proliferation, migration, metastasis, chemo/radio-resistance, and the promotion of epithelial to mesenchymal transition [9,10,18,21,23,[30][31][32]. It has been suggested that signal pathways such as JAK/ STAT1/IRF-1, MEK/ERK/STAT1 and PKD2 etc.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have highlighted the critical role of PD-L1 in regulating the biological functions of cancer cells themselves, including cell proliferation, migration, metastasis, chemo/radio-resistance, and the promotion of epithelial to mesenchymal transition [9,10,18,21,23,[30][31][32]. It has been suggested that signal pathways such as JAK/ STAT1/IRF-1, MEK/ERK/STAT1 and PKD2 etc.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of PD‐L1 in the TME predicts poor prognosis in patients with cancer . Blocking the PD‐1/PD‐L1 pathway has shown promising results in several carcinomas . In this study, we showed that the TME highly expressed PD‐L1 after tumor vaccine therapy.…”
Section: Discussionmentioning
confidence: 53%
“…SA‐IL‐2‐modified vaccine monotherapy increased the proportion of CD4 + Foxp3 + T cells. The high frequency of Tregs could decrease the number of mature DC and disrupt the interactions between DC and T cells by direct contact or by changing the immune microenvironment . Interestingly, adding PD‐1 blockade to SA‐IL‐2‐modified vaccine therapy could reduce the proportion of CD4 + Foxp3 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…PD‐1/PD‐L1 interactions inhibit the functions and proliferation of activated T lymphocytes . Interruption of the PD‐1/PD‐L1 pathway is currently being investigated and has shown promising results in several carcinomas . Upregulation of PD‐L1 in the TME predicts poor survival in patients with cancer .…”
Section: Discussionmentioning
confidence: 99%